An Experimental Study to Explore the Effectiveness of an Online Arabic Teaching Program, to Improve Reading in Native Language (Arabic) in the Country of Asylum for Bilingual Children - Rami Alkhalaf Alabdulla; Abdulrahman Hafed (Türkiye Din Eğitimi Araştırmaları Dergisi)
1.6 million Syrian refugee children live in Turkey due to the war in Syria. Syrian children study in Turkish schools in the Turkish language, but many Syrian families return to Syria for many reasons, which make their children dropping out of school because they are illiterate in Arabic, which is the official language in Syria The aim of the research is to examine the effectiveness of an online intervention program to teach reading in Arabic to displaced Syrian children in Turkey. One intervention group of seven students was selected. Conditions are met: age 8-10 years, the child's mother tongue is Arabic, residing in Gaziantep or Kilis, can't read in Arabic, and Syrian nationality. The reading test was applied before the start of the course, and then the reading test was applied after the course ended. The results indicate that is a significant effectiveness of the online course in teaching reading to children. The results also indicate that the parents' satisfaction with the course is positive.